Dataset for "Mass loss of the Antarctic ice sheet until the year 3000 under a sustained late-21st-century climate" - Chambers, Christopher; Greve, Ralf; Obase, Takashi; Saito, Fuyuki; Abe-Ouchi, Ayako (Zenodo, 2021)
Dataset for the paper "Mass loss of the Antarctic ice sheet until the year 3000 under a sustained late-21st-century climate" (Journal of Glaciology, https://doi.org/10.1017/jog.2021.124 ). Funding acknowledgements: Christopher Chambers, Ralf Greve and Ayako Abe-Ouchi were supported by Japan Society for the Promotion of Science (JSPS) KAKENHI Grant No. JP17H06323. Ralf Greve and Ayako Abe-Ouchi were supported by JSPS KAKENHI Grant No. JP17H06104. Takashi Obase, Fuyuki Saito and Ayako Abe-Ouchi were supported by JSPS Grant-in-Aid for Japan--France Integrated Action Program (SAKURA Program) No. JPJSBP120213203.